Stakeholder expectations, roles and responsibilities in Dutch health promotion for people with intellectual disabilities. (7th September 2018) - Kuijken, N M J; Vlot-van Anrooij, K; van Schrojenstein Lantman-de Valk, H M J; Leusink, G; Naaldenberg, J; Nijhuis-van der Sanden, M W
Summary: This two-phase, qualitative study aims to obtain an overview of stakeholders in the network of people with intellectual disabilities (ID) and their perceived facilitating and hindering factors, expectations, and perceived roles and responsibilities with regard to health promotion. In phase 1, four workshops were conducted to provide insight into involved stakeholders. In phase 2, 29 semi-structured interviews were conducted with stakeholders regarding their views on health promotion. Data were analysed using stakeholder matrices and a combination of domain and thematic analysis. Daily caregivers were identified as the most important and influential stakeholders. Interviewed stakeholders perceived barriers to a healthy lifestyle as relating mainly to the person with ID and, although they stated that people with ID need support to be able to live healthily, there was ambiguity about roles and responsibilities for providing this support. Daily caregivers are not properly facilitated to support a healthy lifestyle. Stakeholders expressed the need for a culture change towards a greater health promotion ethos in care for people with ID. A facilitating context is needed in which the social network supports autonomy and offers opportunities to adapt to physical, social and emotional challenges. Stakeholders see the importance of, and are willing to support, healthy behaviour. They are hindered by a lack of a shared vision and united system in which all stakeholders know their roles and responsibilities. Promotion of a healthy lifestyle should be part of every service provider employee's job and propagated throughout the organization as part of its mission and vision.